Metropolitan region and heritage: bibliometric analysis and systematic review in Brazil - Maltarolo , Maria Heloísa; Miyasaka, Elza Luli; Guimarães, Camila Ferreira; Silva, Fabio Leandro da (ANAP Brazil, 2025)
Objective – This article aimed to examine the state of the art on the theme of cultural and historical heritage in metropolitan regions or urban macro-regions, within both global and national contexts, between 2020 and 2024, to understand heritage dynamics in complex urban environments.Methodology – It was based on bibliometric analysis using research conducted in the Scopus database. From this search, a systematic review of the selected articles was carried out, focusing on those addressing the Brazilian context.Originality/Relevance The concept of heritage is complex, diverse, and encompasses intangible dimensions. The intensification of urbanization and metropolization in Brazil has generated socio-spatial transformations and new urban demands, which in turn have led to a national patrimonialization process. For this reason, both themes are highly relevant to integrated urban planning and must be incorporated into the discussion of public policies.Results – Despite a research gap on the topic, there has been a growing consolidation of cultural heritage studies in metropolitan regions as a recognized research field within academia in recent years. This trend contributes to the advancement of new scientific investigations.Theoretical/Methodological Contributions – The article provides an overview of heritage in complex urban contexts and, methodologically, applies bibliometric analysis and systematic literature review to identify how the subject has been addressed and to highlight existing research gaps.Social and Environmental Contributions – The systematic literature review highlights social perspectives from different angles, such as identity, memory, preservation of historic centers, and heritage education. The analyzed documents contribute to the formulation of public policies, to the sustainable management of urban territories, and to the deepening of scholarly and policy debates.
Keywords: State of the Art; Bibliometrics; Scopus